Room-Temperature CMOS Monolithic Resonant Triple-Band Terahertz Thermal Detector - Xu Wang; Ting-Peng Li; Shu-Xia Yan; Jian Wang (Micromachines, 2023)
Multiband terahertz (THz) detectors show great application potential in imaging, spectroscopy, and sensing fields. Thermal detectors have become a promising choice because they could sense THz radiations on the whole spectrum. This paper demonstrates the operation principle, module designs with in-depth theoretical analysis, and experimental validation of a room-temperature CMOS monolithic resonant triple-band THz thermal detector. The detector, which consists of a compact triple-band octagonal ring antenna and a sensitive proportional to absolute temperature (PTAT) sensor, has virtues of room-temperature operation, low cost, easy integration, and mass production. Good experimental results are obtained at 0.91 THz, 2.58 THz, and 4.2 THz with maximum responsivities of 32.6 V/W, 43.2 V/W, and 40 V/W, respectively, as well as NEPs of 1.28 μW/Hz0.5, 2.19 μW/Hz0.5, and 2.37 μW/Hz0.5, respectively, providing great potential for multiband THz sensing and imaging systems.